A new and exact map of Sweden and Norway corrected from the best observations communicated to the Royal Society at London & the Royal Academy at Paris &c. - Bowen, Emanuel (Made and sold by George Willdey at the corner house in Ludgate street next S:t. Pauls Church London: [s.n.], [1717?], 1717)
Kartta leikattu karttakuvaa reunastavan kehyksen ulkorajaa pitkin. 0-meridiaani: London: Koordinaattiasteikko: W15°-E55°, N75°-53°. Sisältää myös kartakkeen The north part of Norway, Lapland and Greenland. Viistokuva Tukholmasta: A prospect of the city of Stockholm.